Applications of Slide Scan Images of Thin-Sections in Sedimentological Studies (Journal of Pure and Applied Sciences (Science Forum), 2023)
Several conventional and unconventional digitization tools have been used to improve viewingand acquisition of information in the field of sedimentology and sedimentary petrology, ingeology and in science and technology in general. Slide scan images of sedimentary rock thin-sections provide inexpensive, very good, whole thin-section views at magnifications similar tothose of the conventional microscope. This paper demonstrates how slide scan images can beobtained and how they can quickly be used to gather detailed textural, structural andcompositional information of sandstones at microscopic scale. The method has been used instudying features such as grain size, grain shape, fabric, contact between grains, gradedbedding, cross lamination and porosity without the need for polarizing microscope andphotomicrograph. This unpopular, unconventional method is not known by most researcherseven though it can provide alternative means of obtaining vital geological information relevantto both the academia and the industry. This method is also recommended to teachers in low-equipment universities and research centers where research petrological microscopes areeither absent or inadequate or during periods of lock-down.